Pengembangan Usaha Ekonomi Produktif Melalui BUMDes Dalam Mendukung Pemulihan Ekonomi Pedesaan di Kecamatan Konda Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
During the pandemic, the village’s economic condition was also depressed due to a decrease in consumer purchasing power (demand side) and disruption to the price and distribution of agricultural production inputs (supply side). Therefore, the recovery of the village economy is directed at maintaining food security, revitalizing Village-Owned Enterprises (BUMDes), digitizing the economy and cash-intensive work programs which are elaborated by considering the potential and various limitations that each village has. BUMDes which have a core business in managing village economic potential, but their ability to play an economic role in the village is still weak, so it needs to be strengthened to bridge the development of local resources, restore the community’s economy, and become a driving force for the village economy. This service activity is carried out to assist the village government and BUMDes managers in mapping village productive economic businesses, developing BUMDES management as well as introducing village development stakeholders in preparing various development planning documents. With this service, the community of village business actors, BUMDes managers and village officials have the same knowledge and understanding regarding business revitalization through BUMDes development. In addition, the need for BUMDes governance training and assistance both from managerial aspects, business unit (operational) aspects and administrative aspects is fulfilled from this community service activity.